Disequilibrium melting of plagioclase during biotite fluid-absent anatexis of metapelites in the South Marginal Zone of the Limpopo belt, South Africa - Madlakana, Nonkuselo (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.